2015
DOI: 10.1002/lary.25662
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications in superior semicircular canal dehiscence surgery: A systematic review

Abstract: NA Laryngoscope, 126:1218-1224, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 27 publications
1
50
1
3
Order By: Relevance
“…Two other cases who underwent surgery for SSCCD were found to have postoperative significant deterioration in BC PTA without common denominator for these cases. A higher rate of postoperative SNHL was demonstrated with plugging the SSCC through the MFA and with plugging the SSCC in general compared to capping . The use of bone pâté was associated with lower rates of postoperative HL in SSCCD surgeries …”
Section: Discussionmentioning
confidence: 89%
“…Two other cases who underwent surgery for SSCCD were found to have postoperative significant deterioration in BC PTA without common denominator for these cases. A higher rate of postoperative SNHL was demonstrated with plugging the SSCC through the MFA and with plugging the SSCC in general compared to capping . The use of bone pâté was associated with lower rates of postoperative HL in SSCCD surgeries …”
Section: Discussionmentioning
confidence: 89%
“…The use of several materials including bone pâté, perichondrium, cartilage, fascia, cortical bone, and bone substitutes such as hydroxyapatite has been described . We have previously reported on using a construct composed of a fascia underlay and tragal cartilage overlay, held together by Tisseel (Baxter Healthcare) . Most of the patients included in this study underwent resurfacing with a cartilage overlay and an underlay of pericondrium or fascia, supplemented with bone pâté or Tisseel (Baxter Healthcare).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the success of resurfacing in the treatment of SSCD; these have shown mixed results. In a recent meta‐analysis by Giocchini et al, no significant differences in surgical success, defined as complete or partial disappearance of symptoms, was found between resurfacing or plugging. However, a meta‐analysis by Vlastarakos et al determined that resurfacing had a success rate of 50% as compared with 97% for plugging; here, success was defined as symptom resolution.…”
Section: Introductionmentioning
confidence: 91%
“…Háskerputölvusneiðmyndir eru jafnan gerðar til að sýna fram á beineyðinguna. 10 Önnur greiningarleið er svokallað VEMP-próf (Vestibular Evoked Myogenic Potential). Það er próf sem gengur út á að hljóðörvun er gefin í eyrað sem prófað er og síðan er vöðvavirknin í hliðvendivöðva (sternocleidomastoideus muscle) sömu hliðar maeld.…”
Section: Umraeðaunclassified
“…2,10 Sjaldgaeft er að sjúklingar greinist með einkennagefandi rof á bogagöngum. Mögulega stafar það af einkennamyndinni sem er nokkuð sérstök og því að sjúklingar eru ef til vill ekki tilbúnir til að greina frá öllum sínum einkennum.…”
Section: Umraeðaunclassified